AN ANALYSIS OF THE TRANSLATION OF IMAGERY IN “A WALK TO REMEMBER”, A NOVEL BY NICHOLAS SPARKS AND ITS TRANSLATED VERSION “KAN KUKENANG SELALU” - Sulistini Dwi Putranti; Mega Puspa Bonita; Neneng Sri Wahyuningsih (STBA LIA - Jakarta, 2019)
Abtract This study investigates the translation of imagery in A Walk to Remember novel by Nicholas Sparks. This research aims to reveal the types of imagery and the translation techniques applied by the translator in translating imagery. This study uses qualitative method which focuses on describing and explaining the types of imagery found and the techniques applied to deal with imagery. This study uses the theories of imagery proposed by Perrine and Arp (1992), and translation techniques proposed by Molina and Albir (2002). The types of imagery mostly found are visual and organic imagery. The translation techniques used by the translator are adaptation, amplification, borrowing, established equivalent, literal translation, modulation, reduction and transposition. The result of the analysis shows that the techniques mostly used are established equivalent and literal translation. These two techniques are able to reproduce the message from SL to TL without any distortion in meaning. Keyword: visual imagery, organic imagery, translation techniques, established equivalent, literal translation. Abstrak Artikel ini menganalisis penerjemahan imajeri dalam novel A Walk to Remember karangan Nicholas Sparks. Tujuan penelitiannya adalah untuk mengungkapkan tipe-tipe imajeri dan teknik penerjemahan yang diterapkan oleh penerjemah. Penelitian ini menggunakan metode kualitatif agar dapat memerikan dengan baik tipe-tipe imajeri dan teknik penerjemahan yang diterapkan. Kajian ini memakai teori imajeri yang dipaparkan oleh Perrine dan Arp (1992), dan teori teknik penerjemahan yang disampaikan oleh Molina dan Albir (2002). Tipe-tipe imajeri yang banyak muncul dalam novel ini adalah visual dan organik imajeri. Teknik penerjemahan yang diterapkan oleh penerjemah adalah adaptasi, amplifikasi, peminjaman, padanan lazim, literal, modulasi, reduksi, dan transposisi. Hasil analisis menunjukkan bahwa teknik yang paling sering diterapkan adalah padanan lazim dan literal. Kedua teknik ini dapat mereproduksi pesan dari Bsu ke Bsa tanpa mendistorsi maknanya. Kata Kunci: imajeri visual, imajeri organik, teknik penerjemahan, padanan lazim, penerjemahan literal